2022
DOI: 10.1371/journal.pone.0266767
|View full text |Cite
|
Sign up to set email alerts
|

Poisoning among children in Malaysia: A 10-years retrospective study

Abstract: Background Poisoning commonly occurs among children due to their curiosity, where they tend to explore and investigate their surroundings. They frequently put what they find into their mouths as they do not understand the danger and probably cannot read the warning label. As this issue has not been extensively studied in Malaysia; hence, a retrospective analysis of records was carried out to determine the profile of phone call enquiries regarding poisoning among children at the National Poison Centre (NPC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 15 publications
2
14
0
2
Order By: Relevance
“…Among household products, cleaning agents and pesticides were the most common poisoning agents. This is a similar finding to previous studies done in Malaysia 16 and the United States, 17 which also reported cleaning liquids as the common household product in childhood poisoning. Studies from Nepal have reported prescription medication and OP poisoning as the most common agents.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among household products, cleaning agents and pesticides were the most common poisoning agents. This is a similar finding to previous studies done in Malaysia 16 and the United States, 17 which also reported cleaning liquids as the common household product in childhood poisoning. Studies from Nepal have reported prescription medication and OP poisoning as the most common agents.…”
Section: Discussionsupporting
confidence: 92%
“…The duration of hospital stay depends on the type and quantity of poison ingested and the severity of symptoms. The mean hospital stay time in various studies ranges from 0.66 16 , 18 to 17 days. 11 , 13 The mean time of stay in this study was 5.3 days.…”
Section: Discussionmentioning
confidence: 99%
“…These factors together change the exploratory consumption leading to potential accidental poisoning into a common problem in this age group [ 29 ]. The higher prevalence in boys seems to be due to the nature of boys who are more active and adventurous than girls, however, the exact reason is unknown [ 4 , 17 ]. In some studies, the highest frequency of unintentional poisoning has been reported in the age group under 5 years [ 4 , 6 , 16 , 25 ] or 1–3 years [ 19 , 23 , 24 , 31 – 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…considering the poisoning rate in the age group of 6–12 years from previous studies [ 4 ] as p = 82.5, type one error rate α = 0.05 ( Z = 1.96) and precision d = 0.05 resulted 221 samples. , by referring to the registers and using the multi-stage sampling method, 250 cases were selected from among the cases of poisoning during the years 2019–2022.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation